ANALISIS IMPLEMENTASI SISTEM INFORMASI MANAJEMEN (SIM) DI SMK LABOR BINAAN FKIP UNRI PEKANBARU - Jeffri Hunter; Isjoni Isjoni; Azhar Azhar (Universitas Riau, 2022)
The application of information technology will be useful if the application is inaccordance with the goals, vision and mission of the organization with strategic planning and implement strategies into management information systems. So it takes an analysis of various factors that influence the formation of a system strategy plan or information technology that is adaptable and inline with school strategic planning. One technique in analyzing strategic planning and implementation of management information systems strategies is to use valuechain analysis, SWOT and information system success models. This study aim store veal the strategic planning of SIM implementation, obtain an overview of implementation, develop strategic planning so that vision, mission and objective shave been established, and reveal SIM user satisfaction to cloud managerial policies at the Guided LaborVocational School of FKIP UNRI. The conclusion is that the internal factor valueis 0.11 and the external factor valueis 0.02 (the ratio between internal and external factors of 0.11: 0.02) means that internal factors are in a strong position and have the opportunity to support school management to achieve the vision, mission and goals through MIS. With the level of user satisfaction Management Information System (MIS) as a whole is 88.07% derived from the data of 35 respondents. The recommendation of this study is to fully implement the existing SIM, and further research is needed to examine the impact of the implementation of this SIM.